Kształcenie zawodowe w rzemiośle osób z niepełnosprawnością - Bondyra, Krzysztof (Humaniora. Czasopismo Internetowe, 2020)
The article is devoted to the analysis of the potential for counteracting the social exclusion of people with mild intellectual disability through educational and professional activation in craftsmanship. Within the scope of the subject, the author presents the potential of education in craft workshops in Poland and, comparatively, in craft professions in Germany. The article analyses the advantages of vocational training in craftsmanship for counteracting social exclusion, but also shows institutional barriers. The thesis of the article is that, given the large scale of vocational education in crafts in Poland, this type of learning does not fully realise the potential for the professional activation of people with mild intellectual disability. To confirm this, the article presents the activities aimed at introducing a solution concerning the possibility of obtaining qualifications by persons with mild intellectual disability who are learning some craft. These postulated qualifications are described by the Polish Craft Association as a journeyman’s assistant.